Contrasting resistance and resilience to extreme drought and late spring frost in five major European tree species. (17th September 2019) - Vitasse, Yann; Bottero, Alessandra; Cailleret, Maxime; Bigler, Christof; Fonti, Patrick; Gessler, Arthur; Lévesque, Mathieu; Rohner, Brigitte; Weber, Pascale; Rigling, Andreas; Wohlgemuth, Thomas
Abstract: Extreme climate events (ECEs) such as severe droughts, heat waves, and late spring frosts are rare but exert a paramount role in shaping tree species distributions. The frequency of such ECEs is expected to increase with climate warming, threatening the sustainability of temperate forests. Here, we analyzed 2, 844 tree‐ring width series of five dominant European tree species from 104 Swiss sites ranging from 400 to 2, 200 m a.s.l. for the period 1930–2016. We found that (a) the broadleaved oak and beech are sensitive to late frosts that strongly reduce current year growth; however, tree growth is highly resilient and fully recovers within 2 years; (b) radial growth of the conifers larch and spruce is strongly and enduringly reduced by spring droughts—these species are the least resistant and resilient to droughts; (c) oak, silver fir, and to a lower extent beech, show higher resistance and resilience to spring droughts and seem therefore better adapted to the future climate. Our results allow a robust comparison of the tree growth responses to drought and spring frost across large climatic gradients and provide striking evidence that the growth of some of the most abundant and economically important European tree species will be increasingly limited by climate warming. These results could serve for supporting species selection to maintain the sustainability of forest ecosystem services under the expected increase in ECEs. Abstract : There is an urgent need to assess the specific responses of trees to both drought and spring frost to provide solid bases for decision‐making regarding the selection of tree species matching the ongoing environmental change. Using tree‐ring width series from 2, 844 trees from 104 Swiss sites ranging from 400 to 2, 200 m a.s.l. for the period 1930–2016, we found strong disparities in the species resistance and resilience to extreme droughts and spring frosts. Oak, fir, and to a lower extent beech could moderately cope with severe droughts whereas spruce and larch only poorly resist and recover after such events.